Pengaruh Ekonomi Global dan Domestik Terhadap Inflasi di Indonesia - Dini Hariyanti; Soeharjoto Soekapdjo (Universitas Kadiri, 2020)
One of the biggest obstacles for countries economic growth compound is inflation. Government attempted to have lower and stable inflation. Purpose of this research is to determine effect of the global and domestic economy to inflation in Indonesia. Using quarterly time series data from 2009-2018 derived from the Indonesian Economic and Financial Statistics (SEKI), International Financial Statistics (IFS), and Investing. ECM regression model used for this research. For short term, interest rate and exchange rates have positive and significant effect to inflation. But money supply, GDP and oil price not significant, while in long term, interest rate and oil price have positive and significant to inflation, while money supply, GDP and exchange rates are not significant. Government policies are monitoring and anticipating global and domestic fluctuation, by maintaining the stability of interest rate and exchange rates, and also using environmentally friendly alternatives resources, in order to reducing dependence on oil. Besides that, government needs to undertake increasing of GDP to maintain people purchasing power and money supply distribution for productive sector which have biggest adding value by utilizing local resources.